Role of Panchakarma in public health scenario: A Review - Bhushan, Vikram Vir; Sharma, Varun; Puri, Paramjeet (International Research Journal of Ayurveda & Yoga, 2020)
Health is state of complete physical, mental, social well- being and not merely the absence of disease or infirmity’ as defined by WHO. Public health is ‘science of art of preventing disease, prolonging life and promoting health through organized efforts and informed choices of society’. Main aim of Ayurveda science is to maintain health of healthy individual and to cure diseased one. Ayurveda provides better solution in the form of dietary management, life style advices, Panchakarma like detoxification and bio purification procedures, medications. Panchakarma is bio cleansing regimen which includes five procedures helps to brings about homeostasis of body humors, eliminate disease causing complexes from body and check recurrence and progression of disease. If Panchkarma is well supported with effectively scientific documentation and validation then public health concern can be effectively done. In today’s global eras day to day life various toxins and polluted particles and other harmful waste materials are continuously depositing in our body and that causes various disease including mental and physical imbalance. Panchkarma procedures helps to detoxify such toxins and materials by shodhana and prevent disease and enhance the life of society people. Vamana, Virechana Basti Nasya and Raktamokshan fully remove the toxins and make equal level of Doshas and helps to achieve public health scenario.